Hemophilia A subjects with an intron-22 gene inversion mutation show CD4+ T-effector responses to multiple epitopes in FVIII - Gunasekera, Devi; Vir, Pooja; Karim, Ahmad Faisal; Ragni, Margaret V.; Pratt, Kathleen P. (Frontiers in Immunology, 2023)
Background: Almost half of severe hemophilia A (HA) is caused by an intron 22 inversion mutation (Int22Inv), which disrupts the 26-exon F8 gene. Inverted F8 mRNA exons 1-22 are transcribed, while F8B mRNA, containing F8 exons 23-26, is transcribed from a promoter within intron 22. Neither FVIII activity nor FVIII antigen (cross-reacting material, CRM) are detectable in plasma of patients with an intron-22 inversion. Objectives: To test the hypothesis that (putative) intracellular synthesis of FVIII proteins encoded by inverted F8 and F8B mRNAs confers T-cell tolerance to almost the entire FVIII sequence, and to evaluate the immunogenicity of the region encoded by the F8 exon 22-23 junction sequence. Patients/Methods: Peripheral blood mononuclear cells (PBMCs) from 30 severe or moderate HA subjects (17 with an Int22Inv mutation) were tested by ELISPOT assays to detect cytokine secretion in response to FVIII proteins and peptides and to map immunodominant T-cell epitopes. Potential immunogenicity of FVIII sequences encoded by the F8 exon 22-23 junction region was also tested using peptide-MHCII binding assays. Results: Eight of the Int22Inv subjects showed robust cytokine secretion from PBMCs stimulated with FVIII proteins and/or peptides, consistent with earlier publications from the Conti-Fine group. Peptide ELISPOT assays identified immunogenic regions of FVIII. Specificity for sequences encoded within F8 mRNA exons 1-22 and F8B mRNA was confirmed by staining Int22Inv CD4+ T cells with peptide-loaded HLA-Class II tetramers. FVIII peptides spanning the F8 exon 22-23 junction (encoding M2124-V2125) showed limited binding to MHCII proteins and low immunogenicity, with cytokine secretion from only one Int22Inv subject. Conclusions: PBMCs from multiple subjects with an Int22Inv mutation, with and without a current FVIII inhibitor, responded to FVIII epitopes. Furthermore, the FVIII region encoded by the exon 22-23 junction sequence was not remarkably immunoreactive and is therefore unlikely to contain an immunodominant, promiscuous CD4+ T-cell epitope. Our results indicate that putative intracellular expression of partial FVIII proteins does not confer T-cell tolerance to FVIII regions encoded by inverted F8 mRNA or F8B